Overview of Mother's Anxiety in Preparing Children with Autism Spectrum Disorder to Enter the Learning Process - Miratiani Sitompul; Johan Ramadhan Nurwardana (Green Publisher Indonesia, 2026)
Children with special needs need special education services and family support to help them reach their optimal potential. However, parents, especially mothers, often experience anxiety regarding their child's future and development. Factors such as social pressure, past experiences, and children's limitations are the main sources of such anxiety. The purpose of this study is to understand the picture of maternal anxiety in the learning process of children with special needs with Autism Spectrum Disorder (ASD) at Senkids Child Therapy Center of Tangerang Regency. The research method used is a qualitative approach with an experiential narrative method. The main subject in this study is a mother with ASD who is undergoing education in elementary school. Data was collected through semi-structured interviews with the main subjects as well as supporting informants, Data were collected through semi-structured interviews with the main subject as well as supporting informants, such as the subject’s husband and grandmother. Data analysis was carried out using interactive analysis methods, including data reduction, data presentation, and conclusion drawn.